2011
DOI: 10.3177/jnsv.57.48
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Quality of Dietary Amino Acids Composition on the Urea Synthesis in Rats

Abstract: SummaryWe have shown that urinary urea excretion increased in rats given a lower quality protein. The purpose of present study was to determine whether the composition of dietary amino acids affects urea synthesis. Experiments were done on three groups of rats given diets containing a 10% gluten amino acid mix diet or 10% casein amino acid mix diet or 10% whole egg protein amino acids mix diet for 10 d. The urinary excretion of urea, the liver concentration of N -acetylglutamate, and the liver concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Ultimately, higher free AA concentrations in the liver serve as a stimulus for ureagenesis, resulting in less of the dietary-derived AAs becoming available in the systemic circulation to support the postprandial increase in MPS. This notion seems to be confirmed by animal data comparing the ingestion of crystalline AA mixtures, reflecting the AA composition of casein, egg, and wheat protein (61). It was found that the ingestion of the representative wheat mixture resulted in higher free AA concentrations in the liver and subsequent higher ureagenesis than the ingestion of the representative casein and egg mixture.…”
Section: Protein Qualitysupporting
confidence: 60%
See 1 more Smart Citation
“…Ultimately, higher free AA concentrations in the liver serve as a stimulus for ureagenesis, resulting in less of the dietary-derived AAs becoming available in the systemic circulation to support the postprandial increase in MPS. This notion seems to be confirmed by animal data comparing the ingestion of crystalline AA mixtures, reflecting the AA composition of casein, egg, and wheat protein (61). It was found that the ingestion of the representative wheat mixture resulted in higher free AA concentrations in the liver and subsequent higher ureagenesis than the ingestion of the representative casein and egg mixture.…”
Section: Protein Qualitysupporting
confidence: 60%
“…Given that all mixtures were provided as free AAs, differential digestion rates could not have influenced these findings. Therefore, the observed differences in urea production are likely attributed to differences in EAA content of the different protein sources (61). In addition, recent human data by Yang et al (21) showed that the ingestion of soy protein results in higher AA oxidation rates than does whey protein ingestion.…”
Section: Protein Qualitymentioning
confidence: 96%
“…The blood amino acid concentrations rose significantly and peaked one to two hours after ingestion of soy, whereas milk caused a less pronounced rise in blood amino acid concentrations that occurred later [18]. Furthermore, animal models have found that ingestion of wheat protein resulted in higher free amino acid concentration in the liver than the ingestion of representative casein and egg mixtures [19]. Based on these data, we can hypothesize that the significant influx of amino acids after soy consumption, results in a greater increase of deamination in the liver and thus, those amino acids are less available in the blood for a shorter time, as compared to milk protein.…”
Section: Discussionmentioning
confidence: 99%
“…The blood amino acid concentrations rose significantly and peaked one to two hours after ingestion of soy, whereas milk caused a less pronounced rise in blood amino acid concentrations that occurred later [18]. Further, animal models have found that ingestion of wheat protein resulted in higher free amino acid concentration in the liver than the ingestion of representative casein and egg mixtures [19]. Based on this data, we can hypothesize that the significant influx of amino acids after soy consumption, results in a greater increase of deamination in the liver, and thus those amino acids are less available in the blood for a shorter time, as compared to milk protein.…”
Section: Discussionmentioning
confidence: 99%